Turkmen Students at Volgograd State Technical University - L. F. Belyakova; T. L. Sidorova; R. M. Petruneva; V. D. Vasilyeva (Высшее образование в России)
The attractiveness of the University in the world market of educational services is an indicator of its success, which is estimated by a set of criteria including the number of foreign students studying there. For Russian universities, the number of international students is one of the key indicators of internationalization. The authors pay special attention to the criterion of internationalization of higher education in the world ranking of universities. The article provides data related to measures to attract young foreigners to study in higher education institutions of the Russian Federation, including the Volgograd State Technical University. Today, an interest in engineering professions among foreign applicants has increased markedly. The effectiveness of the learning process among foreign students, their achievement levels strongly depend on the success of their adaptation to the new socio-cultural environment. The article addresses the problems of language adaptation of foreign students who came from the former Soviet republics, mainly on the example of students from Turkmenistan.